Vestibular Dysfunction and Difficulty with Driving: Data from the 2001–2004 National Health and Nutrition Examination Surveys - Wei, Eric X.; Agrawal, Yuri (Frontiers in Neurology, 2017)
Background and Objective: There is growing understanding of the role of vestibular function in spatial navigation and orientation. Individuals with vestibular dysfunction demonstrate impaired performance on static and dynamic tests of spatial cognition, but there is sparse literature characterizing how these impairments might affect individuals in the real world. Given the important role of visuospatial ability in driving a motor vehicle, we sought to evaluate whether individuals with vestibular dysfunction might have increased driving difficulty. Materials and Methods: We used data from the 2001 – 2004 National Health and Nutrition Examination Surveys to evaluate the influence of vestibular dysfunction in driving difficulty in a nationally representative sample of U.S. adults aged ≥50 years (n = 3,071). Vestibular function was measured with the modified Romberg test. Furthermore, since vestibular dysfunction is a known contributor to falls risk, we assessed whether individuals with vestibular dysfunction and concomitant driving difficulty were at an increased risk of falls. Results: In multivariate analyses, vestibular dysfunction was associated with a 2-fold increased odds of driving difficulty (odds ratio 2.16, 95% CI 1.57, 2.98). Among participants with vestibular dysfunction, concomitant driving difficulty predicted an increased risk of falls that was significantly higher than in participants with vestibular dysfunction only (odds ratio 13.01 vs. 2.91, p<0.0001). Conclusion: This study suggests that difficulty driving may be a real-world manifestation of impaired spatial cognition associated with vestibular loss. Moreover, driving difficulty may be a marker of more severe vestibular dysfunction.